Smartphone-based ecological momentary assessment (EMA) of alcohol and cannabis use in older adults with and without HIV infection. (August 2018) - Paolillo, Emily W.; Obermeit, Lisa C.; Tang, Bin; Depp, Colin A.; Vaida, Florin; Moore, David J.; Moore, Raeanne C.
Abstract: Introduction: Ecological momentary assessment (EMA) has been used to characterize substance use among adult populations; however, little is known about the validity of EMA and the patterns and predictors of substance use among older adults with and without HIV infection. Methods: Thirty-five (22 HIV-positive, 13 HIV-negative) older adults aged 50–74 were assessed for 14 days and completed up to four smartphone-based surveys per day. Results: Participants completed an average of 89.5% of possible EMA surveys. EMA self-reported alcohol and cannabis use were significantly positively correlated with laboratory-assessed, self-reported days of alcohol ( r = 0.52, p = 0.002) and cannabis ( r = 0.61, p < 0.001) used and quantity of alcohol ( r = 0.42, p = 0.013) and cannabis ( r = 0.41, p = 0.016) used in the 30 days prior to baseline assessment. In a subset of 15 alcohol or cannabis users, preliminary analyses of the effects of mood and pain on alcohol or cannabis use showed: 1) greater anxious mood predicted substance use at the next EMA survey ( OR = 1.737, p = 0.023), 2) greater happiness predicted substance use later in the day ( OR = 1.383, p < 0.001), and 3) higher pain level predicted substance use earlier in the day ( OR = 0.901, p = 0.005). Conclusions: Findings demonstrate that EMA-measured alcohol and cannabis use has convergent validity among older adults with and without HIV infection. Preliminary results showing predictors of substance use highlight the importance of gathering EMA data to examine daily variability and time-dependent antecedents of substance use among this population. Highlights: Ecological momentary assessment of substance use shows validity in older adults. Greater anxiety predicts subsequent substance use. Greater happiness predicts substance use in the evening/at night. Higher pain level predicts substance use in the morning.